Prioritizing Training Needs for Nurses in the Government Hospitals of the Ha’il Region, Saudi Arabia: Future Directions for Educational Developers - Pasay-an, Eddieson; Alsrour, Hatem Homoud (UI Scholars Hub, 2022)
Background: The assessment of training needs can help establish the current performance or knowledge levels related to certain essential nursing activities. The purpose of this study is to determine the training needs of the staff nurses of the government hospitals in Ha’il Region, Saudi Arabia. Methods: This study employed a cross-sectional–correlational approach with 230 staff nurses of the government hospitals in the City of Ha’il. Random sampling was used to ensure the representativeness of the sample. Results: The nurses perceived training activities as very important (6.22 ± 1.09) in their work but performed the necessary activities only moderately (5.21 ± 1.44). Position was strongly positively correlated with management (r = 0.796; p < 0.003). In terms of current performance, age had a strong positive correlation with administration (r = 0.659; p < 0.001) and management (r = 0.675; p < 0.001). The participants suggested quality management system (96%) as the area that is most in need of training. Conclusions: Findings on the importance of training needs suggest that positions were strongly positively correlated with management. With regard to the perceived current performance, age had a strong positive correlation with administration and management. The participants suggested quality management system as the area that is most in need of training.